Association Between Visual Acuity and Prospective Fall Risk in Generally Healthy and Active Older Adults: The 3-Year DO-HEALTH Study - Wieczorek, Maud (2024)
Although aging has a strong impact on visual acuity (VA) and falls, their interaction is understudied in generally healthy older adults. This study aimed to examine if and to what extent baseline VA is associated with an increased risk of all and injurious falls over 3 years in generally healthy community-dwelling older adults.